Measurement of Productivity and Efficiency of Potato Production in Two Selected Areas of Bangladesh: A Translog Stochastic Frontier Analysis - Begum, A; Imam, MF; Alam, MA (Progressive Agriculture, 2013)
Some partial analyses were used to determine the productivity of potato production. The per hectare potato production of the farmers of Lalmonirhat Sadar and Aditmari Upazila were 19897.88 and 21208.47 kg respectively. The benefit-cost ratio in Lalmonirhat Sadar and Aditmari Upazila were 1.52 and 1.56 respectively. The coefficient of farm size was positively significant in Aditmari in the inefficiency effect model, which meant large farmer was economically less efficient than small farmer. The sign of education was negative and significant, which indicates that inefficiency decreases with the increase of education in Aditmari Upazila. The economic efficiency varied from 81 to 99% at aggregate level, 97 to 99% in Lalmonirhat Sadar and 72 to 99% in Aditmari Upazila. The mean economic efficiencies were 98, 97 and 96% for Lalmonirhat Sadar, Aditmari Upazila and at aggregate, level respectively. There appeared to be 2, 3 and 4% economic inefficiencies for Lalmonirhat Sadar, Aditmari and all regions, respectively. This indicates that the cost of production could be reduced on an average by 4% keeping the output constant at the aggregate level. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16780 Progress. Agric. 21(1 & 2): 233 - 245, 2010